Between History and Anthropology: A Review of The Great Cat Massacre and Other Episodes in French Cultural History by Robert Darnton - Rakhimzhanova, A.; Küçükbekir, E. (KU Publ., 2021)
This article-review examines some important aspects of Historical Anthropology on the basis of Robert Darnton’s book The Great Cat Massacre. We believe that Historical Anthropology is a useful instrument in learning and understanding various social and cultural processes. In this case, Darnton’s work represents a good example of such work. In order to understand the culture and mentality of French people from the eighteenth century, Darnton analysed different sources such as folktales, personal letters, diaries, and policeman’s reports. This article discloses methods of understanding history via anthropology and vice versa. It can be a useful source for both historians and social anthropologists.
Тарихи антропология: Роберт Дарнтонның «Мысықтардың ұлы қырғыны және француз мәдени тарихындағы тағы басқа эпизодтар» атты кітабына шолу
Историческая антропология: обзор книги Роберта Дарнтона «Большая кошачья резня и другие эпизоды французской истории культуры»
Keywords: historical anthropology; folklore studies; cultural history; French history